Attributes of graduate architects: An industry perspective - Salleh, R. (Medwell Journals, 2016)
The purpose of this study is to reveal the industry's viewpoint on the importance of attributes of graduate architects. Data were collected from Malaysian architecture firms, using a structured questionnaire. Of the 250 distributed questionnaires, 65 completed were returned, with a response rate of 26. Descriptive statistical analysis was performed to assess the level of importance for each graduate attribute. The results indicate that of those attributes proposed, responsibility, a positive attitude and teamwork skills were rated as the top three attributes. This study contributes to the existing literature on employability skills by providing industry perspective on the subject, which is, thus far, less discussed in existing published research. Implications of the findings are discussed. Â© Medwell Journals, 2016.